Uso de método enzimático para elaboração de saquê a partir de arroz longo ou curto, tipo 1 ou gessado - Menezes, Paulo Roberto Ribeiro (2024)
Brazil produced 10,788.8 thousand tons of rice, with long rice being the largest production due to its popularity in Brazilian cuisine. From this production, approximately 1% exhibits a completely opaque color similar to gypsum in the grain when husked and polished, thus being referred to as chalky rice or "barriguinha" when the grain is partially chalky. This characteristic is not accepted by the Brazilian population due to its appearance. Currently, the rice industry classifies and separates these grains; studies indicate that the population accepts a maximum of 10% of this rice in lower-value commercial packaging for type 5 rice. This work aims to develop a protocol for sake production utilizing long chalky rice through in vitro enzymatic saccharification, comparing it to short rice suitable for sake production, as well as short chalky rice. To achieve this, a mashing ramp was developed with enzymes derived from Aspergillus oryzae (α-amylase, β-amylase), followed by glucoamylase. This ramp was then applied to two types of rice (long and short) with two polishing levels (30% and 40%) and two classifications (normal and chalky), inoculated with Saccharomyces cerevisiae, followed by Saccharomyces bayanus on the eighth day of fermentation. The fermentation products showed an alcohol content in accordance with legislation, characterized as dry without the need for the addition of agricultural-origin potable ethanol, thus producing sake classified as Junmai Daiginjo-shu. The total production time was optimized, being shorter than the traditional method.